Aplicación del modelo estadístico Monte Carlo para predecir la rentabilidad de la flota de movimiento de tierras en el proyecto El Toro - Constructora FRELMAR S.A.C - Taboada Custodio, Sairy Terry (2023)
The general objective of this work was to predict the profitability of the earthmoving fleet of the construction company FRELMAR S.A.C. Making use of a study of the quantitative, experimental, longitudinal, correlational, comparative application type; The sample consisted of 93 data on the income and costs of the 1103 dump truck used in the haulage system, from October 2020 to December 2021. Observation was used as the data collection technique, the main instrument being the field notebook and the valuations as primary source. The simulations were made for two dump trucks in two scenarios, in the first scenario, considering the probability distributions obtained from the historical data, there was a NPV of -$9,476.58 ± 156 with a 31.34% probability that the fleet is profitable, in the second scenario the variants of the daily effective hours were generated with the triangular distribution function coded by the author. As a result, the profitability acquired a NPV of $32,564.66 ± 187.4 with a 93.09% probability of being profitable, concluding that the profitability of the earthmoving fleet at Constructora FRELMAR S.A.C for the period 2022 to 2026, with 50% of probability of having a NPV of -$9,476.58 ± 156 at 95% confidence compared to a 31.34% probability of being profitable. For the second scenario, it was observed that the earthmoving fleet is only profitable if the inoperative days (in mechanical failures and preventive maintenance) are less than or equal to 13% during the service period.